A Rose by Another Name Would Smell the Same: Hidden Potential of Antisystem Parties in Slovakia? - Černěnko, Tomáš, 1981-
Voter attitudes, based on the results of parliamentary elections in 2020, towards European integration, universal left-right integration, religious attitudes in politics, the rights of ethnic minorities, the position between national and cosmopolitan sentiments and political decentralization in favour of regions at the district level of Slovakia. Factors, affecting voter's selection.